Analgesia through FKBP51 inhibition at disease onset confers lasting relief from sensory and emotional chronic pain symptoms - Sara Hestehave; Roxana Florea; Samuel Singleton; Alex J. H. Fedorec; Sara Caxaria; Oakley B. Morgan; Katharina Tatjana Kopp; Laurence A. Brown; Tim Heymann; Shafaq Sikandar; Felix Hausch; Stuart N. Peirson; et al. (Proceedings of the National Academy of Sciences, 2025)
Chronic pain affects 20 to 30% of the population and imposes a significant socioeconomic burden as it is often accompanied by substantial emotional comorbidities such as anxiety and depression. Yet, the mechanisms underlying the interactions between the sensory and emotional aspects of chronic pain remain poorly understood. Here, we investigated the role of FKBP51, a regulator of the stress response, in mediating both sensory and emotional symptoms of chronic pain. Inhibition of FKBP51, via genetic deletion or pharmacological blockade, in persistent joint pain reduced fast-onset sensory, functional and activity-related symptoms, as well as late anxio-depressive comorbidities. FKBP51 inhibition after the establishment of the hypersensitive state provided only temporary symptoms relief, while acute inhibition at disease onset protected from the full development of sensory and anxio-depressive symptoms for up to 6 mo. Our results also indicated that early pain symptoms could predict the late sensory and emotional outcomes of chronic pain. RNA sequencing of spinal cord tissue revealed that late FKBP51 inhibition transiently altered nociceptive genes associated with mechanical hypersensitivity. In contrast, early inhibition persistently downregulated the Naaa gene, a key regulator of the transition to chronic pain, and reorganized spinal cilia. Our results indicate that early FKBP51 inhibition after injury can persistently reduce chronic pain and prevent the onset of associated emotional comorbidities by modulating critical spinal neurobiological pathways that play pivotal roles in the transition to chronic pain.